Development of a high-density linkage map and chromosome segment substitution lines for Japanese soybean cultivar Enrei. (24th November 2017) - Watanabe, Satoshi; Shimizu, Takehiko; Machita, Kayo; Tsubokura, Yasutaka; Xia, Zhengjun; Yamada, Tetsuya; Hajika, Makita; Ishimoto, Masao; Katayose, Yuichi; Harada, Kyuya; Kaga, Akito
Abstract: Using progeny of a cross between Japanese soybean Enrei and Chinese soybean Peking, we developed a high-density linkage map and chromosomal segment substitution lines (CSSLs). The map consists of 2, 177 markers with polymorphism information for 32 accessions and provides a detailed genetic framework for these markers. The marker order on the linkage map revealed close agreement with that on the chromosome-scale assembly, Wm82.a2.v1. The differences, especially on Chr. 5 and Chr. 11, in the present map provides information to identify regions in the genome assembly where additional information is required to resolve marker order and assign remaining scaffolds. To cover the entire soybean genome, we used 999 BC3 F2 backcross plants and selected 103 CSSLs carrying chromosomal segments from Peking in the genetic background of Enrei. Using these low-genetic-complexity resources, we dissected variation in traits related to flowering, maturity and yield into approximately 50 reproducible quantitative trait loci (QTLs) and evaluated QTLs with small genetic effects as single genetic factors in a uniform genetic background. CSSLs developed in this study may be good starting material for removing the unfavourable characteristics of Peking during pre-breeding and for isolation of genes conferring disease and stress resistance that have not yet been characterized.